HYDRODYNAMICAL CHARACTERISTICS OF BINH CANG - NHA TRANG WATERS FROM MODELS: FEM AND ECOSMO - Chung, Tran Van; Long, Bui Hong (Vietnam Journal of Marine Science and Technology, 2014)
This paper has focused on the hydro-dynamical characteristics of Binh Cang - Nha Trang waters from 2 models: ECOSMO (finite difference) and FEM (finite element) based on the last observed data of the VAST’s project, code: VAST 07. 04/11-12. The seasonal currents simulated by FEM showed the existence of local eddies in the top of Nha Phu lagoon. Meanwhile, they have not been detected by ECOSMO (because the best stabilization of ECOSMO is achieved for the minimum depth of 2.0 meters). In addition, the spatial distances from the mesh grids of finite difference have had restrictions for modelling current regimes at coastal borders, islands, reefs, etc., as well as in the cases that the particular representation of local characteristics of small space configurations (the mouth of small rivers with complicated topography) is required. In this paper, some calculated results about self-cleaning capabilities (water exchange, residential water ...) of reseached water body have been persented.